Distraction, not hunger, is associated with lower mood and lower perceived work performance on fast compared to non-fast days during intermittent fasting. (June 2015) - Appleton, Katherine M; Baker, Stephanie
Using a repeated measures design, 16 females recorded hunger, distraction, mood and perceived work performance on two consecutive fast days, on two earlier and on two subsequent consecutive non-fast days, during intermittent fasting. Using regression analyses, low positive mood was associated with higher distraction ( β  = −0.38, p  < 0.01), and lower perceived work performance was associated with higher distraction ( β  = −0.50, p  < 0.01) and lower positive mood ( β  = 0.59, p  = 0.01). No associations were found with hunger (largest β  = −0.11, p  = 0.15). Associations between mood, perceived work performance and distraction but not hunger mirror those found in traditional dieting and suggest no benefit for attention from intermittent fasting-type regimes.